استراتيجية جيش التحرير الوطني في مواجهة خط موريس 1959 م. -1960 م. - كمون، عبدالسلام سفاح Kamoun, Abdulsalam Saffah (جامعة باتنه 1 - كلية العلوم الإسلامية, 2020)
تعد الثورة الجزائرية (1962 -1954م) من أعظم ثورات العالم في القرن العشرين، لما شهدته من أحداث سياسية وتطورات عسكرية طيلة سبع سنوات ونصف، واجه خلالها جيش التحرير الوطني- ذو الإمكانيات المادية المحدودة- أعتى وأقوى دولة استعمارية آنذاك، ورغم ذلك استطاعت وحدات جيش التحرير الوطني- لاسيما على الحدود – تحقيق عدة انتصارات ضد قوات الاحتلال الفرنسي كان لها الأثر العميق على المستويين الإقليمي والعالمي. كما أن الغرض من هذه الورقة البحثية يكمن أساسا في الوقوف الفاحص على نشاط وجهود جيش التحرير الوطني على الجبهة الشرقية، واستراتيجيته العسكرية في مواجهة خط موريس المكهرب الذي أنشأته إدارة الاحتلال الفرنسي على الحدود الجزائرية الشرقية عام 1957م قصد شل حركة الثوار والمجاهدين نحو الداخل والخارج، ومن ثم إبطال مفعول القواعد الخلفية للإمداد اللوجستيكي التي شكلتها قيادة الثورة في تونس.
The Algerian Revolution (1954-1962) is one of the world greatest twentieth-century revolutions, because of the political events and military developments for seven and a half years, during which the National Liberation Army - with limited material resources - faced the strongest and mightiest colonial state at the time. Nevertheless, the National Liberation Army units, especially on the borders, managed to achieve several victories against the French occupation forces, and this had a profound impact on the regional and global levels. The purpose of the present research is mainly to examine the activities and efforts of the National Liberation Army on the eastern front, and its military strategy in the face of the electrified Maurice line established by the French occupation administration on the eastern Algerian border in 1957. The aim of this line was to paralyze the movement of the Algerian fighters, thereby disrupting the logistic supply provided by the rear bases established in Tunisia by the Revolutionary Command.
Keywords: الاحتلال الفرنسي للجزائر -- حركات التحرر الوطني -- ثورة التحرير الجزائرية -- العمليات العسكرية